Blood, land, and sex : legal and political pluralism in Eritrea - Favali, Lyda, 1969- (Indiana University Press, 2003)
In Eritrea, state, traditional, and religious laws equally prevail, but any of these legal systems may be put into play depending upon the individual or individuals involved in a legal dispute. Because of conflicting laws, it has been difficult for Eritreans to come to a consensus on what constitutes their legal system. In Blood, Land, and Sex, Lyda Favali and Roy Pateman examine the roles of the state, ethnic groups, religious groups, and the international community in several key areas of Eritrean law - blood feud or murder, land tenure, and gender relations (marriage, prostitution, rape).